História oral e memória do cotidiano das práticas religiosas da pessoa idosa em situação asilar - Gomes, Margarida Maria Silva (2013)
The number of elderly in the end of the twentieth first century has been increasing and is now a reality also found in Brazil and in the state of Paraíba, considered the fifth state in the Northeast region with larger elderly population. Allied to these changes is added the emergence of a greater number of institutionalized elderly, due to new social, cultural and family patterns. Technological advances brought new features, previous diagnoses in medicine, surgery and pharmacology, providing more effective therapeutic and care interventions, have led a significant number of people to reach the age increasingly high. This new population profile raised the question of institutionalization, where some aspects have contributed to the significant increase in long-stay institutions for the elderly (ILPIs): the insertion of women in the labor market, reducing the number of children per family and the levels of chronic degenerative diseases common in this age group. In this context the practice of religion the daily life of the asylum institution serves as an anchor to better meet the challenges, whether personal or group living, because religion, religiosity and spirituality help in facing the old age with security, hope and faith of better days. The research aimed to analyze the history and oral memory of the daily of religious practices of the elderly in asylum situation, construct a theoretical referential about the theme in question and trace the socio-demographic profile of eight elderly women users of one of the six ILPIs of the municipality of João Pessoa and of that institution. It is an exploratory, descriptive bibliographical and documental research, with qualitative and quantitative approaches, focusing an institution located in the Jardim Cidade Universitária neighborhood. The instruments for data collection were: semi-structured interview and in loco observations, using a diary of notes and records of the elderly women who participated in the survey. A remarkable characteristic in the researched ILPI is the clientele composed of 34 women, all with compromised health, aged between 60 to 107 years old, but the sample was of 8 women between 60 and 84 years old. In relation to socio-demographic data, it was found that: 47% were single, 12.5% married and others, among widowed and separated, totaled 50%, data that address the issue of no ability of skill families, who do not know take care of their elderly. 75% were born in the state of Paraíba, 12.5% were from Pernambuco and 12.5% of Espírito Santo, most is brought by relatives or the Public Prosecution of Paraíba. On admission an social and care evaluation is made. 62.5% are users between 6 months to 2 years, 12.5% were 3-4 years, and 25% are over 4 years. Regarding religion, 75% are Catholics, 12.5% are Protestant and 12.5% are Spiritualists. During the interviews the elderly women said that, before coming to the ILPI, professed another religious practice, but as the ILPI professes the Catholic religion, they accept or, in the silence of his room, profess their practice of origin that gives comfort and hope for better days.